2011
DOI: 10.1002/asi.21681
|View full text |Cite
|
Sign up to set email alerts
|

What's skill got to do with it?: Information literacy skills and self‐views of ability among first‐year college students

Abstract: This study replicates a previous study based on work in psychology, which demonstrates that students who score as below proficient in information literacy (IL) skills have a miscalibrated self-view of their ability. Simply stated, these students tend to believe that they have above-average IL skills, when, in fact, an objective test of their ability indicates that they are below-proficient in terms of their actual skills. This investigation was part of an Institute of Museum and Library Servicesfunded project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(153 citation statements)
references
References 16 publications
5
136
0
5
Order By: Relevance
“…In the area of information literacy, Gross and Latham (2007, 2012 replicated the research of Dunning and Kruger; in two out of three studies, they identified a disconnect between students' self-assessments of their information literacy skills and their actual skill level. Other studies also compared peoples' self-reported IL skills and their actual performance, but the existence of Dunning-Kruger Effect has been inconclusive.…”
Section: Article ]mentioning
confidence: 52%
“…In the area of information literacy, Gross and Latham (2007, 2012 replicated the research of Dunning and Kruger; in two out of three studies, they identified a disconnect between students' self-assessments of their information literacy skills and their actual skill level. Other studies also compared peoples' self-reported IL skills and their actual performance, but the existence of Dunning-Kruger Effect has been inconclusive.…”
Section: Article ]mentioning
confidence: 52%
“…It has since been replicated in the field of grammar (e.g. Pavel, Robertson, & Harrison, 2012) and found in other domains, such as chemistry (Bell & Volckmann, 2011;Pazicni & Bauer, 2014), information literacy (Gross & Latham, 2012), and emotional intelligence (Sheldon, Dunning, & Ames, 2014). Based on previous paragraphs, we predict the following:…”
mentioning
confidence: 92%
“…Information is organized in complex ways, and can be difficult to find and to evaluate. We recognize that, for most people, confidence in information skills exceeds actual skill level (Gross & Latham, 2012). Many people do not understand the context of information-how or why it is produced, nor the purposes for which different types of information are made available.…”
Section: Challenges To Developing Information Literacymentioning
confidence: 99%